Representation of TikTok Viral Trends on Generation Z Communication Behavior (Case Study of 2021 STISIPOL Candradimuka Palembang Students) - Efridah, Eka; Nirmala, Sila (Sinergi International Journal of Communication Sciences, 2026)
This study investigates the representation of TikTok's viral trends within the communication behavior of Generation Z students at STISIPOL Candradimuka Palembang. Previous studies have primarily emphasized aspects of consumption, psychological impact, or branding, consequently leaving the dimension of media representation and everyday communication practices among local students largely underexplored. The research employs a descriptive qualitative approach, utilizing the theoretical framework of Media Representation (Hall, 1997) combined with Uses and Gratifications theory (Katz et al., 1973). This combined perspective examines how students interpret viral trends, what specific motivations underlie their use of TikTok, and crucially, how these derived motives are translated into observable, concrete communication patterns. Five active students from the 2021 cohort served as key informants, selected based on their criteria as intensive users with experience participating in viral challenges or creative content creation within the TikTok ecosystem. Data were meticulously collected through semi-structured interviews exploring narratives of experience, alongside content observations on informants' TikTok accounts, and digital documentation (videos, comments, screenshots). Analysis using the Miles–Huberman interactive model revealed five salient dimensions of communication behavior representation: use goals (entertainment, social recognition), identity initiatives (content experimentation, self-branding), competitive arenas (personal branding, popularity metrics), self-awareness (social comparison, reflexivity), and value orientation (speed, visual dominance, orientation toward virality). The findings demonstrate that TikTok functions as a powerful representation space, shaping Gen Z communication behavior through social validation, and an algorithmic culture that directs relevance. TikTok's viral trends thus act as cultural codes organizing how students understand themselves and their digital public interactions.